Idiopathic pulmonary haemosiderosis: a form of microscopic polyarteritis? - Leaker, B (1992)
Idiopathic pulmonary haemosiderosis remains a diagnosis of exclusion in patients who present with pulmonary alveolar haemorrhage. Systemic vasculitis developed in a patient with an eight year history of idiopathic pulmonary haemosiderosis. The diagnosis was confirmed by a rising titre of antineutrophil cytoplasmic antibodies directed against myeloperoxidase. Treatment with immunosuppressive agents resulted in complete resolution of symptoms and suppression of the antibodies. Measurement of antineutrophil cytoplasmic antibodies is recommended for all patients with pulmonary alveolar haemorrhage syndromes.